2019
DOI: 10.1111/jar.12647
|View full text |Cite
|
Sign up to set email alerts
|

The double‐edged sword of vulnerability: Explaining the persistent challenges for practitioners in supporting parents with intellectual disabilities

Abstract: Background Evidence suggests that parents with intellectual disabilities can be “good enough” parents with appropriate support that focuses on the whole family. This paper brings together theories of vulnerability with an ethics of care approach to reflect on challenges for practitioners in supporting parents, drawing upon data from a study carried out in Scotland. Method An online survey was administered to practitioners in three settings, and follow‐up interviews were carried out with key informants. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Describing families as vulnerable can increase the barriers in accessing appropriate support and a constructive collaboration [37]. The emotional strain caused by experiencing their own child as a burden when negotiating with a professional caring system may cause conflict to both the parents themselves and the collaborating efforts [38]. Although these families felt burdened, local research has documented that such families have a robustness and a family structure similar to typical families, with an even higher proportion of lasting marriages or cohabitation [37].…”
Section: Burden Of Careoffers Respite Carementioning
confidence: 99%
“…Describing families as vulnerable can increase the barriers in accessing appropriate support and a constructive collaboration [37]. The emotional strain caused by experiencing their own child as a burden when negotiating with a professional caring system may cause conflict to both the parents themselves and the collaborating efforts [38]. Although these families felt burdened, local research has documented that such families have a robustness and a family structure similar to typical families, with an even higher proportion of lasting marriages or cohabitation [37].…”
Section: Burden Of Careoffers Respite Carementioning
confidence: 99%
“…Describing families as vulnerable can increase the barriers in accessing appropriate support and a constructive collaboration (36). The emotional strain caused by experiencing their own child as a burden when negotiating with a professional caring system may cause con ict to both the parents themselves and the collaborating efforts (37). Although these families felt burdened, local research has documented that such families have a robustness and a family structure similar to typical families, with an even higher proportion of lasting marriages or cohabitation (36).…”
Section: Burden Of Care -Offers Respite Carementioning
confidence: 99%
“…Recent concepts of practitioners' constructions of families as 'vulnerable' have suggested that such a label can be negative on their perceived capacity to parent. Describing families as vulnerable can increase the barriers in accessing appropriate support and a constructive collaboration (34)]. The emotional strain caused by experiencing their own child as a burden when negotiating with a professional caring system may cause con ict to both the parents themselves and the collaborating efforts (35).…”
Section: Burden Of Care -Offers Respite Carementioning
confidence: 99%